2D DOA Estimation of Wideband and FH Signals Using Improved K-means Clustering and Implementation Considerations - Zahra Memarian; Mahdi Majidi (Iranian Journal of Electrical and Electronic Engineering)
This paper presents a two-dimensional (2D) direction of arrival (DOA) estimation method based on the popular correlative interferometer (CI) approach, incorporating practical considerations. Leveraging the flexibility of software-defined radio (SDR) platforms, the proposed array antenna model is designed according to the specifications of a dual-channel synchronous USRP B210 receiver and an appropriate RF switch. To enhance the speed and accuracy of 2D DOA estimation for narrowband, wideband (WB), and frequency hopping (FH) signals, this study introduces a method that integrates power spectrum density (PSD) and spectrogram analysis of the receiver’s instantaneous bandwidth with an optimized filter bank, to precisely detect active frequencies and their intervals. Additionally, a fast, modified K-means clustering algorithm is developed to refine DOA estimation for FH and WB signals across multiple active subchannels. Simulation results demonstrate improved DOA estimation accuracy in multipath conditions, particularly at longer distances, with further enhancements achieved through the proposed clustering method.